A multiband circular polarization selective metasurface for microwave applications - Syed Muhammad Qasim Ali Shah (Nature Portfolio, 2021)
Abstract In this research article, a multiband circular polarization selective (CPS) metasurface is presented. A reciprocal bi-layered metasurface is designed by introducing the chirality in the structure. The top layer of the proposed metasurface is composed of circular split-ring resonator with a cross shape structure inside it. The same structure is printed on the bottom side of the proposed metasurface by rotating it at an angle of 90° to achieve chirality in the structure. The proposed metasurface is able to add CPS surface capability between 5.18 and 5.23 GHz for y-polarized incident wave. For the frequency band of 5.18–5.23 GHz, the transmission goes up to − 4 dB, while the polarization extinction ratio (PER) reaches up to − 27.4 dB at 5.2 GHz. Similarly, for x-polarized incident wave, three strategic CPS operating bands are achieved within the frequency ranges of 10.64–10.82 GHz, 12.25–12.47 GHz, and 14.42–14.67 GHz. The maximum PER of 47.16 dB has been achieved for the 14.42–14.67 GHz frequency band at 14.53 GHz. Furthermore, the response of the metasurface does not vary against oblique incidences up to 45°. The simple structure, angular stability, multiband and miniaturized size make this metasurface an outstanding applicant for polarization conversion and biomedical applications.